2021
DOI: 10.1136/bmjopen-2020-047102
|View full text |Cite
|
Sign up to set email alerts
|

Exploring patient safety outcomes for people with learning disabilities in acute hospital settings: a scoping review

Abstract: ObjectivesTo produce a narrative synthesis of published academic and grey literature focusing on patient safety outcomes for people with learning disabilities in an acute hospital setting.DesignScoping review with narrative synthesis.MethodsThe review followed the six stages of the Arksey and O’Malley framework. We searched four research databases from January 2000 to March 2021, in addition to handsearching and backwards searching using terms relating to our eligibility criteria—patient safety and adverse eve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 74 publications
0
10
0
1
Order By: Relevance
“…Early identification and prevention of adverse events, poor communication and management of these events such as reporting delays and omissions of care (as reported in adult, parent and child literature) or specific issues such as medication and procedural adverse events have not been identified in this review (Oulton et al, 2016, 2020; Tuffrey‐Wijne, Goulding, Giatras, et al, 2014; Tuffrey‐Wijne, Goulding, Gordon, et al, 2014). A recent scoping review by Louch et al (2021) reports the need for further research in understanding patient safety and adverse events including exploring protective factors and potential explanatory mechanisms: identifying patient safety interventions, improvement initiatives, recommendations and examples of good clinical practice for children and adults with intellectual disability (Louch et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Early identification and prevention of adverse events, poor communication and management of these events such as reporting delays and omissions of care (as reported in adult, parent and child literature) or specific issues such as medication and procedural adverse events have not been identified in this review (Oulton et al, 2016, 2020; Tuffrey‐Wijne, Goulding, Giatras, et al, 2014; Tuffrey‐Wijne, Goulding, Gordon, et al, 2014). A recent scoping review by Louch et al (2021) reports the need for further research in understanding patient safety and adverse events including exploring protective factors and potential explanatory mechanisms: identifying patient safety interventions, improvement initiatives, recommendations and examples of good clinical practice for children and adults with intellectual disability (Louch et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…A recent scoping review by Louch et al (2021) reports the need for further research in understanding patient safety and adverse events including exploring protective factors and potential explanatory mechanisms: identifying patient safety interventions, improvement initiatives, recommendations and examples of good clinical practice for children and adults with intellectual disability(Louch et al, 2021).…”
mentioning
confidence: 99%
“…In a narrative synthesis of academic and grey literature by Louch et al, people with learning disabilities experienced poorer safety outcomes in hospital. However, these were ameliorated when family and carers were involved and informed staff were able to meet the needs of people with intellectual disability 32 . A scoping review conducted by Kokorelias et al 33 found that using a family‐centred care approach improved the well‐being of those with illness and/or disability and their family/caregivers through mutual inclusion, communication, and partnerships.…”
Section: Discussionmentioning
confidence: 99%
“…Discriminatory practices have even led to fatalities for a number of patients with I/DD (Spassiani et al, 2020). The literature highlighted: (a) persons with I/DD experienced variations in the quality of care received, (b) healthcare providers and society at large shared negative perceptions regarding disabilities, (c) knowledge deficits and attitudes were related, (d) exposure to these patients led to positive attitudes, and (e) patients with I/DD and nurses could benefit from including disability teaching in the nursing curriculum (Appelgren et al, 2018;Desroches et al,, 2019;Doyle et al, 2016;Louch 2021). Gaps in intellectual disability education resulted in inconsistencies in the preparation of nurses and quality-of-care for these patients (Appelgren et al, 2018).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Assessment problems led to nurses identifying these patients as demented or babies. With identification and assessment issues in mind, nurses would find it difficult to tailor care for this group(Louch, 2021;Spassiani, 2020). Nurses in this study reported organizational policies and systems obstacles to providing care, such as nurse-patient ratios and heavy workloads.…”
mentioning
confidence: 92%